Animal Welfare in Public and Private Standards and On-Farm Compliance - Dominic Norbert Annen; Christine Wieck; Markus Kempen (German Journal of Agricultural Economics (GJAE), 2013)
This paper evaluates the animal welfare situation on cattle farms in Germany and Austria applying a multidimensional assessment framework. Using minimum requirements formulated in public legislation and private certification schemes, animal needs indices are calculated. They are subsequently compared with results from on-farm surveys. Most private certification schemes address animal welfare in their requirements but this does not necessarily result in higher levels of farm animal welfare if they only overlap with existing national standards. The on-farm evaluations showed that most farms already voluntarily over-comply with some of the standards imposed by public legislation or private labels. Thus, proposals to simply increase standards to improve farm animal welfare without considering the already implemented on-farm animal welfare level have to be evaluated with caution.
Keywords: 330; Tierschutz; Rinderhaltung; Deutschland; Österreich